THICKNESS DEPENDENCE OF MAGNETIC SWITCHING DYNAMICS OF BARIUM-FERRITE AS A HIGH-DENSITY PERPENDICULAR MAGNETIC STORAGE MEDIA (Department of Physics, Faculty of Mathematics and Natural Sciences, 2017)
Micromagnetic study of material thickness dependence of Barium-ferrite nano-dot magnetization dynamics has been performed. The used materials characteristics in this research represent the properties of Barium-ferrite. Barium-ferrite was modeled as a nano-dot with a surface area of 50 Ã— 50 nm2 and its thickness varies from 5 nm to 100 nm. This nano-dot was simulated using micromagnetic simulator software by solving Landau-Lifshitz-Gilbert equation. According to this study, obtained that the Barium-ferrite nano-dot has excellent thermal stability. Magnetization rate of this nano-dot decreases exponentially with the increase of thickness. The fastest magnetization rate observed in 5 nm of nano-dot thickness, meanwhile 45 nm for the slowest rate. Magnetization reversal mode of this Barium-ferrite nano-dot is dominated by domain wall nucleation and propagation. During the propagation of the domain wall, the exchange interaction becomes the main aspect compared to the other contributed energies.